Medical Leech Therapy (Attai Vidal) In Siddha Medicine-A Review - Miraaj, R.; Sailajah, S. (Global Academic Research Institute, 2020)
Siddha medicine, traditional system of healing that originated in South India and is considered to be one of India & #39;s oldest systems of medicine. Siddha is a comprehensive system that places equal emphasis on the body, mind, spirit and restore the innate harmony of individual. In Siddha system diseases were classified in to 4448. In Siddha system of medicine, the diseases were treated in many ways like Mani, Manthiram, Avizhtham, Yogam and Varmam. Avizhtham (Medicine) is one way to treat the diseases in Siddha medicine, which is further divided into 32 internal medicine and 32 external medicines. Attaividal (leech therapy) is an external blood letting therapy of application of medicinal leech to remove blood from the affected area and give relieve distension,remove pus & slough and drain the discharge. The aim of the study is to review the Attaividal from different Siddha literatures and research articles. Seven books were selected from library of Unit of Siddha Medicine & University of Jaffna. Data were collected and analysed and the leech therapy was described by various Siddhars in their literature, Particularly the Siddhar Agastiyar and Therayar who explained leech therapy elaborately in their text Agasthiyar erandayiram, Agasthiyar ranavaithiyam and Agasthiyar nayanavithi & Therayar Tharu. According to Therayar Tharu, Attai vidal is placed in twenty seventh place. Attai Vidal (Medicinal leech therapy) is also called as Hirudo therapy on the basis of commonly used leech species, Hirudo medicinalis. Medicinal leeches are used in the treatment of various diseases such as benign tumors, swelling, Kiranthi, haemorroids, abscess and boils, contusion, varicose ulcer, varicose vein, deep vein thrombosis, rheumatoid arthritis, skin and musculoskeletal diseases, arthritis, dysmenorrhea, eye diseases, traumatic swelling. Many studies have found that leeches have various bioactive molecules in their secretions. such as Hirudin, hyaluronidase, collagenase, histamine like molecules, anaesthetics, fibrinases, antibacterial, etc. This is concluded that the leech therapy was used in Siddha and other system of medicine for various medical and surgical conditions. The Scientific studies on leech saliva were proven and support the leech application in Siddha system of medicine
Keywords: Siddha; Attaividal; Leech therapy; Hirudin